Andrographis paniculata mitigates first-line anti-tubercular drugs-induced nephrotoxicity in Wistar rats. (19th May 2022) - Sharma, Varsha; Sharma, Radhika; Sharma, Vijay Lakshmi
Abstract: Context: Anti-tubercular drugs (ATDs) mediated adverse drug reactions are major concerns for clinicians to treat tuberculosis infection. This study aimed to investigate Andrographis paniculata extract-based phytotherapy to combat the nephrotoxic effects caused by ATDs therapy. Methods: Reno-protective effect of A . paniculata extract in ATDs-induced rats was evaluated through LPO, GSH, CAT, SOD, GST, urea, creatinine, uric acid, and histopathological studies. Standardization of the extract was performed using RP-HPLC and FTIR analysis. Whereas, the effect of A. paniculata extract on ATDs induced genetic perturbation was analyzed using micronucleus assay. Moreover, the expression level of the xenometabolic gene was investigated using RT-PCR to explore the therapeutic mechanism. Results: The nephrotoxic effect of ATDs was indicated by elevated levels of LPO and renal function markers along with the reduced activity of renal antioxidants. An up-regulated expression profile of NAT gene and histological alterations were observed in renal tissue however, micronucleated PCEs were observed in bone marrow cells. Concomitant treatment with A. paniculata extract revealed a noticeable amelioration of elevated oxidative stress markers, gene expression levels, genotoxic perturbation, and histological alterations in a dose-dependent manner. Conclusion: Hence, the present study using A. paniculata leaf extract confirmed to play effective phytotherapy against ATDs induced renal toxicity.